A constituição do herói no cinema brasileiro contemporâneo - Adriano Medeiros da Rocha (2015)
This research seeks to show that symbolic elements are being used for constituting the hero myth in contemporary Brazilian cinema and how these elements are being orchestrated. For this, the definition of the concept of hero and identification of its main dramatic purposes was necessary. The approach of this object with the Brazilian cinema took place from the perception of some fundamental aspects of the cultural identity of this country and its people. Regarding the temporal boundaries, we chose to work with a cut started from the Brazilian Cinema Resume period, in the 1990s, continuing to the present day. Establishing the same cut, also sought to demonstrate that period and the main characteristics of the produced film productions. Continuing this way, it also have been proposed case studies, selecting three brazilian movies full-length (Lamarca - 1994; Central Station - 1998, and Tropa de Elite 2 - 2010) for the development of in-depth filmic analysis which had as a base a thorough look at the structures and narrative strategies used and the builder profile of the protagonists heroes.